Clinical researchStudy of the sperm immobilizing action of furacin - Rana, Kumkum; Das, Srijit (Archives of Medical Science, 2007)
Introduction: Semen is not azoospermic immediately after vasectomy. Accidental conception after surgery can ruin the popularity of a sterilization programme and also marital relations. It has been found that furacin can be used to immobilize sperm and hence cause sterilization. Material and methods: We studied sperm immobilization with furacin in 20 human adult men in the age group 25 to 45 years. Also, the vas deferens of 12 sexually mature male guinea pigs were irrigated with furacin on one side and normal saline on the other side to rule out tissue toxicity. Histological sections of vas of both sides were prepared and compared. Results: In the semen samples of healthy adult males, with furacin concentration of ł0.4 mg/ml sperm were found to be immotile in all the fields in 5:1 dilution at 37°C. The histological sections of vas deferens of guinea pigs also revealed no evidence of any inflammatory response. Conclusions: Thus it was observed that furacin has the ability to immobilize sperm in certain concentrations and is nontoxic to the vas deferens of guinea pigs. The use of furacin as a post-vasectomy flush can be recommended to ensure early and complete contraception.